Chromosome numbers, RAPD and ISSR profiles of six Zingiber species found in Manipur, India - LAISHRAM BIDYALEIMA; RAJKUMAR KISHOR; GURUMAYUM JITENDRA SHARMA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Bidyaleima L, Kishor R, Sharma GJ. 2019. Chromosome numbers, RAPD and ISSR profiles of six Zingiber species found in Manipur, India. Biodiversitas 20: 1389-1397. The present investigation was done to assess the cytological information and genetic relationships among six species of Zingiber, viz., Zingiber capitatum, Z. kangleipakense, Z. kerrii, Z. montanum, Z. officinale and Z. zerumbet found in Manipur, North-East India. The somatic chromosome numbers observed were 2n = 22 for Zingiber capitatum, Z. kerrii, Z. montanum, Z. officinale and Z. zerumbet, whereas Z. kangleipakense showed tetraploidy with 2n = 44. The somatic chromosome numbers of Zingiber kangleipakense and Z. kerrii are reported for the first time. Randomly amplified polymorphic DNA (RAPD) and inter-specific sequence repeat (ISSR) molecular markers were employed to reveal the genetic relationships among the six species. The pair-wise Jaccard genetic similarity varied from 0.518 to 0.658 for RAPD and from 0.436 to 0.682 for ISSR data. Dendrogram derived from the combined data of RAPD and ISSR clustered the six members into two groups. The detected polymorphism level represents high genetic distance at the inter-species level, and introduces RAPD and ISSR as efficient markers for the assessment of genetic relatedness in Zingiber. Our results may provide useful information for application in breeding, conservation and utilization.